Luca Pedroli (ed.), L'analogia nuziale nella Scrittura. Saggi in onore di Luis Alonso Schökel (The Nuptial Analogy in the Holy Scriptures. Essays in Honor of Luis Alonso Schökel), (Pontificia Università Gregoriana – Pontificio Istituto Biblico: Roma 2019) - Bardski, Krzysztof (The Biblical Annals, 2020)
Book Review: Luca Pedroli (ed.), L'analogia nuziale nella Scrittura. Saggi in onore di Luis Alonso Schökel (The Nuptial Analogy in the Holy Scriptures. Essays in Honor of Luis Alonso Schökel), (Pontificia Università Gregoriana – Pontificio Istituto Biblico: Roma 2019)